ANALISIS PENGARUH MEDIA INFORMASI, TINGKAT PENDIDIKAN DAN PENGETAHUAN HALAL TERHADAP PERSEPSI MASYARAKAT MENGENAI PENERAPAN WISATA HALAL (STUDI DI KECAMATAN PAMIJAHAN KABUPATEN BOGOR) - Muhamad Yaya Supriadi; Ujang Buchori Muslim; Hasbi Ash Shiddieqy (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
The potential for halal tourism in Indonesia is quite large, but one of the obstacles to the halal tourism industry in Indonesia is the lack of public understanding regarding government regulations, concepts, as well as the challenges and potential of halal tourism, which is one of the obstacles that causes Indonesian halal tourism to be considered less popular. so that knowledge related to these aspects of halal tourism is needed. The purpose of this study was to analyze the perception of the people of Pamijahan District on the application of halal tourism. This type of research is quantitative with a sample of 66 respondents. The sampling technique used was the Random Sampling technique with the Tabachic & Fidell method. The analytical method used in this study is multiple linear regression analysis using SPSS version 25 software. The results of this study show the effect of perceptions of the application of halal tourism which consists of information media, level of education and knowledge of halal together has real and positive influence. However, it is more dominant that halal knowledge has a significant and positive effect on the perception of the application of halal tourism, with a variable regression coefficient value of 0.807, which means that if halal knowledge increases by one unit, then the perceived value of implementing halal tourism will increase by 0.807. Increasing knowledge and awareness of halal (halal awareness) in the Pamijahan sub-district community can encourage an increase in the development of halal tourism in the region.